The effects of lupin (lupinus angustifolius) protein isolation on its dietary fibre and whey proteins - Coorey, Ranil; Chao, K.; Kumar, Vivek; Jayasena, Vijay (Wiley-Blackwell Publishers, 2013)
This study was conducted to evaluate the effects of protein isolation on dietary fibre and whey proteins of lupin flour. Commercially available flour was used in-order to understand the possible commercial applications of the results generated by the project. Protein isolation process from lupin flour that was first defatted, resulted in three products: (1) the dietary fibre fraction; (2) the protein isolate; and (3) the soluble lupin whey protein supernatant. The total dietary fibre (TDF), insoluble dietary fibre (IDF) and soluble dietary fibre (SDF) contents in the flour were 28.9, 19.1, and 9.9%, respectively. The TDF, IDF and SDF of the dietary fibre fractions were 72.1, 65.8 and 6.3% respectively. A salting out process for the isolation of the whey protein fraction with different salts including trichloroacetic acid was evaluated. Emulsification and foaming properties of the whey proteins were significantly affected by the type of salt. The functional properties of the control whey protein isolated by a simple additional centrifugation step were significantly better than those isolated with any of the salts. The results showed that the lupin whey protein with good functional properties can be produced from the whey fraction.